Choroidal Variations in Diabetic Macular Edema: Fluorescein Angiography and Optical Coherence Tomography. (2nd January 2018) - Wang, Xiangning; Li, Shuting; Li, Wei; Hua, Yanjun; Wu, Qiang
ABSTRACT: Purposes : To (i) evaluate variations in choroidal thickness (CT) and choroidal volume (CV) in diabetic macular edema (DME), as demonstrated by fluorescein angiography (FA) and enhanced depth-imaging (EDI) optical coherence tomography (OCT) (EDI-OCT) and (ii) correlate these variations with visual acuity. Methods : This study was a retrospective observational case series of patients with diabetic retinopathy (DR) and DME. The study groups comprised 77 DR patients ( n  = 87), all of whom underwent color fundus photography, FA, and OCT on the same day. The control group comprised 25 age-matched healthy individuals ( n  = 50 eyes). CT was measured by manual segmentation (EDI-OCT built-in automated retinal segmentation software). Variations in CT in DME patterns were analyzed. Results : We studied a total of 87 eyes from patients with DR, including 50 eyes from 25 patients with DME (DME group) and 37 eyes from 22 patients without DME (non-DME group). For DME-group patients, mean subfoveal choroidal thickness (SFCT) and total CV (TCV) were 258.8 ± 81.7 µm and 6.6 ± 1.8 mm 3, respectively. For non-DME group patients, mean SFCT and TCV values were 247.6 ± 73.3 µm and 6.6 ± 1.6 mm 3, respectively. SFCT and TCV values for both groups were significantly lower than for healthy controls (294.3 ± 87.6 µm and 7.7 ± 1.8 mm, 3 respectively) ( p  = 0.040 and 0.019, respectively). CTs varied according to morphological FA and OCT patterns of DME, but did not differ significantly ( p  > 0.05). Conclusions : CT and CV in DR patients were decreased compared with healthy controls. CTs did not differ significantly between DME patterns demonstrated by OCT and FA.